KOMUNIKASI DALAM LINGKUNGAN PEMBELAJARAN ONLINE: SEBUAH STUDI BIBLIOMETRIK - Nuryadin, Asep (Communications, 2023)
This study aims to conduct a bibliometric analysis of articles related to communication in an online learning environment. The Publish or Perish application was used to collect data on articles published in 2012-2022 in Google Scholar-indexed journals. Then, the data were processed using Microsoft Excel and VOSViewer applications. The first finding in this study was that of the 242 identified articles, the number of articles published fluctuated between 2012-2019 before continuing to increase from 2020 to 2022. This increase was also in line with the COVID-19 pandemic, which forced educational institutions to choose online learning as the main model of organizing learning. Second, of the 20 articles with the most citations, two concepts often related to communication in an online learning environment were collaboration and satisfaction with learning. Third, of the 118 terms distributed into 10 clusters, some of the terms that appeared most frequently besides those related to communication and learning were COVID, pandemic, and student. Fourth, the most recent term was child, which indicated that there were at least three publications related to this term, followed by other terms such as mathematical communication, online learning communication, online teaching, communication strategy, college, virtual education, lecturer, pandemic, and online. learning process. Based on these findings, the researcher provides several recommendations.